Kajian Analisis Strategi Belajar Pada Anak Berkebutuhan Khusus Jenjang Sekolah Dasar (SD) - Qolbie, Lu’luil; Imroatun, Imroatun; Hanifah, Balqis Mutiara; Munawaroh, Hidayatul (rogram Studi Pendidikan Guru Madrasah Ibtidaiyah (PGMI) Fakultas Tarbiyah dan Ilmu Keguruan Institut Agama Islam Tarbiyatut Tholabah (IAI TABAH) Lamongan, 2023)
Children with special needs (ABK) have different characteristics from one another. Therefore, children with special needs must have special educational services that are tailored to the abilities possessed by these children according to their potential. Inclusive education is an education system intended for children with special needs. With the meaning of inclusive education as a system of providing education to students who have abnormalities and potential intelligence or special talents, ABK has different potential abilities. In this way the learning strategy that is applied to ABK is the application of remedial teaching learning which helps teachers understand and set certain conditions in learning.